Use of Electronic Transmission by Agricultural Communications News Units - Marlene A. Fritz (Journal of Applied Communications, 1993)
Agricultural communications units in all 50 states were surveyed as to their use of electronic transmission of news releases, either computer-to-computer or via posting to electronic bulletin boards